Plan estratégico de marketing para la distribuidora de helados Eskimo de la ciudad de Loja, provincia de Loja - Romero Ordoñez, Mercedes Betzabe (2016)
This paper entitled "STRATEGIC MARKETING PLAN FOR THE DISTRIBUTION OF ICE CREAM ESKIMO CITY OF LOJA Loja province, was developed in order to perform an analysis of the current situation, identifying weaknesses and strengths, and suggest alternative solutions. The overall objective in the present work was based was: Develop a Strategic Marketing Plan for the Distribution of Ice "Eskimo" city of Loja. Historical (company history), Descriptive analytical (description information), deductive (proposals, strategies), inductive (conclusions and recommendations): In research, the methods employed. The techniques used were observation, interview applied to the Manager of the company, the survey applied to 9 230 internal customers and external customers of the company. The evaluation of internal (Matrix EFI) results in the weighted total 2.45 meaning that the distributor of Eskimo Ice Cream, if you have internal problems that need to be addressed, for which strategies to eliminate existing weaknesses raised. For its part the evaluation of external factors (EFE Matrix) had a weighted total of 2.44, indicating that the Eskimo Ice Cream Distributor is within an environment that provides opportunities to address threats. By analyzing SWOT Matrix High Impact was built, which identified strategic alternatives that may be developed for the benefit of the company they are: To promote the products of the company through various mass media and more coverage, Structuring a training program to improve work efficiency in the company, Performing Incentive Plan for employees of the company, in order to improve performance, increase sales through promotional incentives. The total cost of the objectives is $ 5.980.00. The conclusions that were reached after completion of the work is set: Lack of a Strategic Marketing Plan, do not set a mission, vision and values that determine who they are, who they want to be in the future, and how to get it, do not invest in Advertising as a strategy that allows to create a preference for ESKIMO product on the bids of competitors, there is no training plan for employees of the Distributor, which directly affects the customer, they have not defined a Plan promotions, to convey the qualities of products (Eskimo) to customers, so that the device is driven to acquire, increased staff productivity due to the lack of an incentive plan is not encouraged. Main recommendations are suggested: You need to apply a Strategic Marketing Plan for Eskimo Ice Cream Distributor, city of Loja, to achieve the same position in the minds of consumers and increase their sales. Advertising implement the Plan suggested, which displays a message and a budget to the different channels of mass communication, to achieve the best outcome of effectiveness and economy. Train staff, considering they are the most valuable resource of the company, hence the need to invest in training plans in order to improve knowledge and skills of staff working in the Distributor. Implement a promotional plan, aiming to grow in the market, create loyalty in customers and increase brand presence in the market. Develop Incentive Plans, which will help to encourage a participatory environment to achieve greater integration and commitment of staff.